VAKSIN CORONA VIRUS DISEASE 2019 - Anggun Elidya; Innou Dhanu; Rani Himayani; Helmi Ismunandar; Ghalib Nasser (Medula, 2021)
Corona Virus Disease 19 (COVID-19) is a virus that emerged at the end of 2019 which is known to have originated of Wuhan which is the capital of Hubei Province, China. Based on data from the World Health Organization (WHO) until January 31, 2021, 235 countries were infected with COVID-19 and 103 million sufferers worldwide and the death rate reached 2,220,000 with symptoms include high fever, difficulty breathing and coughing, and recognition of these symptoms takes 2 to 14 days after infection. Prevention of COVID-19 can be stopped by early detection, isolation and vaccine administration. The mRNA vaccine is an mRNA encoding antigen that is translated in the host's cellular machine by vaccination. This type of vaccine has a self-amplifying genomic structure that causes extreme RNA replication in the cytosol, such as the example of Pfizer BioTech with the name BNT162 (3 LNP-mRNAs) entering its third phase. Deactivated Virus-Based Vaccine (PiCoVacc) is the development of a conventional vaccine starting with in-vitro neutralization and isolating strands of the SARS-CoV-2 virus. This type of vaccine is the SARS-CoV-2 vaccine (inactivated) which has been distributed to several countries such as Turkey, Brazil and Indonesia by administering two times (0 14) intramuscularly (0.5cc). Subunit vaccines are vaccines that include one or more antigens that can stimulate the host immune system. The DNA vaccine is a vaccine consisting of a plasmid DNA molecule encoding one or more antigens and a SARS-CoV-2 (Ad5-nCoV) Adenovirus Type-5 Vector-Based Vaccine which uses the recombinant adenovirus type 5 (Ad5) vector through spike glycoproteins from the Covid strand -19.